Peningkatan motivasi dan prestasi belajar mahasiswa melalui model Project Based Learning pada mata kuliah Pendidikan Agama Islam - Fahmi Huda, Rofiazka; Firdiawan Ekaputra (Indonesian Journal of Islamic Religious Education, 2023)
This study aims to determine (1) whether there is an increase in learning motivation through the application of project-based learning model (2) whether there is an increase in learning achievement through the application of project-based learning model. This study used a pre-experimental design with one class of research samples. The sample used in this study were students of the Agribusiness Study Program in semester 1 of Jambi University. Data collection techniques in this study used questionnaire instruments and questions. Data on motivation and learning achievement were analyzed using a paired sample t-test. The results showed (1) an increase in learning motivation through the application of the project-based learning model (2) an increase in learning achievement through the application of the project-based learning model. Based on this study's results, the project-based learning model can increase student motivation and learning achievement, especially for Jambi University Agribusiness students. Therefore, it is recommended that project-based learning models be used in Islamic Religious Education lectures to increase student motivation and learning achievement.